Electron energization and mixing observed by MMS in the vicinity of an electron diffusion region during magnetopause reconnection. Issue 12 (28th June 2016) - Chen, Li‐Jen; Hesse, Michael; Wang, Shan; Gershman, Daniel; Ergun, Robert; Pollock, Craig; Torbert, Roy; Bessho, Naoki; Daughton, William; Dorelli, John; Giles, Barbara; Strangeway, Robert; et al.
Abstract: Measurements from the Magnetospheric Multiscale (MMS) mission are reported to show distinct features of electron energization and mixing in the diffusion region of the terrestrial magnetopause reconnection. At the ion jet and magnetic field reversals, distribution functions exhibiting signatures of accelerated meandering electrons are observed at an electron out‐of‐plane flow peak. The meandering signatures manifested as triangular and crescent structures are established features of the electron diffusion region (EDR). Effects of meandering electrons on the electric field normal to the reconnection layer are detected. Parallel acceleration and mixing of the inflowing electrons with exhaust electrons shape the exhaust flow pattern. In the EDR vicinity, the measured distribution functions indicate that locally, the electron energization and mixing physics is captured by two‐dimensional reconnection, yet to account for the simultaneous four‐point measurements, translational invariant in the third dimension must be violated on the ion‐skin‐depth scale. Key Points: Distribution functions of accelerated meandering electrons in the diffusion region are observed Effects of meandering electrons on the electric field normal to the reconnection layer are detected Mixing of the inflowing and exhaust electrons shapes the exhaust flow pattern